Algunos problemas provenientes de la Teoría de Rayos Aplicada a las Ecuaciones de Onda Sísmica - Piedrahita Escobar, Carlos César (Ingeniería, 2013)
This paper gives an overview of the application of ray theory in the seismic wave equations, in particular, to P wave propagation. In addition, a couple of open problems that are obtained from the analysis using ray theory are stated. These problems have an academic interest in their mathematical formulation, and also have a practical application in Exploration and /or Production Geophysics.